Neuroplastizität und Sport - Reinsberger C (Deutsche Zeitschrift für Sportmedizin, 2015)
Sports and exercise can influence brain structure and function on a variety of levels. Adult hippocampal neurogenesis, synaptic plasticity, dendritic complexity and angiogenesis are among the basic mechanisms that are induced by exercise in ani mal models. But how do these mechanisms translate into the human brain and provide the basis for many positive aspects of sports and exercise on neurological and even neurodegenerative diseases?Knowledge of exercise induced adult neurogenesis and plasticity on synaptic and cellular levels is primarily derived from rodent models. Evidence for similar effects in human brains are evident mainly at a macroscopic level and take into account the hierarchical and modular network organization of the human brain that can be assessed in vivo by a growing number of neuroimaging methods. Besides further elucidating the complexity of the basic mechanisms themselves, many studies lack a differentiated view on the intervention of exercise or sports.It will be most interesting and helpful to understand in the future, how adult neurogenesis and brain plasticity are influenced by type (e.g. cardiovascular, coordination, strength), volume and intensity of exercise. With this knowledge it would be possible to regard and utilize sports and exercise rather like a pharmacy than a single medication by designing disease specific exercise and sports specific training programs that may most effectively restore and/or enhance brain function, one of the great challenges of Sports Medicine in the years to come.KEY WORDS:neuroplasticity, adult neurogenesis, sports, exercise, neuroimaging